2015 International Conference on Advances in Computer Engineering and Applications 2015
DOI: 10.1109/icacea.2015.7164647
|View full text |Cite
|
Sign up to set email alerts
|

A priority based job scheduling algorithm using IBA and EASY algorithm for cloud metaschedular

Abstract: Job scheduling (JS) is one of the most important issues in a Cloud system. The objective of job schedulers in cloud computing is to meet users' requirements and optimize the utilization of cloud resources. To achieve better QoS with high resource utilization in a cloud environment, an improved backfill algorithm (IBA) using balanced spiral (BS) method can be used. Results show that IBA minimizes resource idleness up to a great extent. However, IBA does not provide support for handling job priority and QoS. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Further research is conducted to remove the compromises between QoS parameters and load balancing. [83][84][85][86] Table 3 enlists the QoS parameters that are considered by proposed algorithms and frameworks. It can be observed that none of the studies has considered every parameter in their frameworks.…”
Section: Existing Solutions To Overcome the Mentioned Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is conducted to remove the compromises between QoS parameters and load balancing. [83][84][85][86] Table 3 enlists the QoS parameters that are considered by proposed algorithms and frameworks. It can be observed that none of the studies has considered every parameter in their frameworks.…”
Section: Existing Solutions To Overcome the Mentioned Challengesmentioning
confidence: 99%
“…Both the mentioned algorithms result in efficient resource scheduling at the cost of not considering security and privacy. Further research is conducted to remove the compromises between QoS parameters and load balancing 83‐86 …”
Section: Cloud Computingmentioning
confidence: 99%
“…Heuristic, meta-heuristic, and optimization-based are three categories of task scheduling schemes. Heuristic task scheduling schemes can be divided into quite a few sub categories based on their objectives such as load balancing [27], [28], [29], priority-based scheduling [30], [31], [32], , task duplication [33], and clustering [34].…”
Section: Prior Workmentioning
confidence: 99%
“…Dubey et.al [5] proposed a dynamic algorithm that is based upon the priority of task using the combined approach of IBA and EASY algorithm. There are various dynamic job scheduling algorithm also exist in cloud environment but the entire algorithm have some pros and cons.…”
Section: Fig1 Metascheduler Architecturementioning
confidence: 99%
“…After applying IBA algorithm all queues are combined to form a intermediate sequence. 5. Now applying the EASY algorithm on this intermediate sequence for better utilization of resources.…”
mentioning
confidence: 99%